Effectiveness of Cognitive Behaviour Therapy on Academic Procrastination Behaviour of Secondary School Students in Ika-South Local Government Area, Delta State (Journal of Guidance and Counselling Studies, 2021)
Academic procrastination is a cognitive as well as a behavioural problem among students during which students continues to delay a task that can have serious effects on them whose lives are characterized by frequent postponements or by perfectionists who want to do their best. Studies have shown that academic procrastination cannot be corrected by medical procedures rather by the use of some psychological techniques such as cognitive behaviour therapy. The study therefore investigated the effectiveness of cognitive behaviour therapy on academic procrastination behaviour of secondary school students in Ika-South Local Government Area of Delta State. Three research questions and three null hypotheses guided the study. The study adopted pre-test, post-test control group (quasi- experimental research design). The population of study consisted of 920 secondary school students. Purposive sampling procedure was used to select two schools out of 20 existing co-educational ones in Ika- South Local Government Area. The participants identified with academic procrastination were 80 JSS111 students preparing for their external examination. Instrument for data collection was adopted from Sunitha and Musthafa’s Academic Procrastination Scale (APS) Nigerian used. The internal consistency reliability coefficient for Nigeria sample is 0.74.The experimental group were subjected to the treatment. Data were analyzed using Mean for research questions while the null hypotheses were tested at .05 Per cent level of significance using ANCOVA. The findings revealed that there was a significant effectiveness of the cognitive behaviour therapy on the treatment of academic procrastination more than conventional counselling. It was recommended among others that the Delta State Ministry of Education should provide on-the job training through seminars, symposia and workshops to school guidance counsellors and other allied professionals on the use of cognitive behaviour therapy in reducing academic procrastination behaviour and other behavioural problems among secondary school students.